Positive smoking cessation-related interactions with HIV care providers increase the likelihood of interest in cessation among HIV-positive cigarette smokers. Issue 10 (3rd October 2017) - Pacek, Lauren R.; Rass, Olga; Johnson, Matthew W.
ABSTRACT: Smoking cessation has proven to be a challenge for HIV-positive smokers. Patient and provider characteristics may provide barriers to smoking cessation. We aimed to identify characteristics associated with interest in cessation as well as characterize use of, current interest in, and provider recommendations for smoking cessation modalities. Data came from 275 HIV-positive smokers recruited online. Half (49.1%) of the sample was interested in quitting; daily smoking was associated with decreased likelihood of interest in cessation, whereas making a lifetime quit attempt, receiving encouragement to quit from an HIV care provider, and greater frequency of discussions regarding cessation with HIV care providers were associated with increased likelihood of interest in cessation. Nicotine replacement therapy was the most commonly used (42.9%), generated the most interest (59.1%), and was the most commonly clinician-recommended (70.7%) cessation modality. Findings emphasize the importance of the healthcare provider-patient relationship for smoking cessation promotion in HIV-positive smokers.